Roberto Cantillano Vindas: On the Transformation of His Music Into Quartets for Low Brass - Chinchilla Meza, Iván (2025)
For a significant part of Costa Rican history, national music was developed within military bands, not only in terms of training performers, honing skills, and popularizing a musical culture, but also in terms of creation. Compositions serving political figures, institutions, and elements of popular culture gradually formed our musical heritage, which the Archivo Histórico Musical of the Escuela de Artes Musicales preserves, studies, and revives, and which Cuadernos de las Artes now presents in this series of studies by Iván Chinchilla Meza. This fourth Cuaderno de las Artes is evidence of this work to rescue our musical heritage, in this case, dedicated to the work of composer Roberto Cantillano Vindas (1887-1955), who was a flutist in the military bands of Alajuela and San José, as well as director of the San José Military Band (1919-1936) and general director of Costa Rica's bands (1936-1948). It was during his time as conductor that he explored his talent as a composer, which is now being recovered, studied, and brought to the present for the enjoyment of new generations.